EVALUATION OF POTATO GERMPLASM FOR ADAPTABILITY AND RESISTANCE TO LATE BLIGHT - Kaushik, S. K.; Bhardwaj, Vinay; Singh, P. H.; Singh, B. P. (Potato Journal, 2013)
International Potato Center (CIP), Lima, Peru has developed germplasm with improved horizontal resistance to late blight free of R genes. Nineteen germplasm accessions were imported from CIP and evaluated for their late blight resistance and adaptability under hill conditions in India. Six germplasm accessions had high yield and resistance to late blight. Use of these accessions as parents in the late blight breeding programme will help in combating this dreaded disease besides broadening the genetic base of future potato cultivars.